The article Response of Two Rice Varieties Grown using SRI Method in Two Different Locations - Nalwida Rozen (JERAMI : Indonesian Journal of Crop Science, 2018)
Application of system of rice intensification (SRI) method has been considered as one of powerful efforts to increase the harvested yield by modifying the plant and itssurrounding environment. This study was aimed to determine the effect of different environment towards the response of rice varieties grown using SRI method. Two rice varieties, Batang Piaman and IR-42 were grown in District of Tanjuang Barulak (Regency of Tanah Datar) and District of Saniang Baka (Regency of Solok). Plant height and several yield parameters, such as productive tillers, panicle length, grain number per panicle, and yield per plot were assessed from both varieties and locations. Statistical analysis was conducted using randomized block design (RDB) and significance was further evaluatedusingDuncan’s New Multiple Range Test (DNMRT) with a p>0.05. Batang Pariaman appeared in taller performance than IR-42. Regarding the number of productive tiller, Batang Piaman resulted more productive tillers in Solok, while IR-42 was dominant in number of productive tiller compared to Batang Piaman in Tanah Datar. Unlike IR-42, Batang Piaman exhibited longer panicle, more grain amounts per panicle, and higher yield per plot than IR-42 in both locations.